POLYMER DEGRADATION IN TURBULENT DRAG REDUCING FLOWS IN PIPES - Sandoval, G. A. B.; Trevelin, R.; Soares, E. J.; Silveira, L.; Thomaz, F.; Pereira, A. S. (Revista de Engenharia Térmica, 2015)
The drag reduction by addition of high molecular additives has been investigated by a number of researchers since it was reported by Toms more than 60 years ago. One of the most significant limitations in drag reduction is the polymer degradation, which is caused by the turbulent structures. Researches have demonstrated that many parameters affect the polymer efficient, as: molecular weight, Reynolds number, concentration and temperature. In the present work we investigate this degradation phenomenon in a pipe flow apparatus device, for aqueous solutions of three different polymers: Polyethylene Oxide (PEO), Polyacrylamide (PAM) and Xanthan Gum (XG).The first two are known as flexible molecules while the last one is considered rigid. The dependence of polymer scission on molecular weight, concentration and Reynolds number is analyzed. We report how the drag reduction decreases when the flow pass repeatedly through the pipe and how the pressure loss measured in the apparatus increases, despite to the fact that the experiment was conducted at a fixed inlet pressure. It is worth noting that the mechanism of loss of efficiency for the XG solutions seems to be completely different from that observed for PEO and PAM, the flexible materials.